Dopamine transporter availability in alcohol and opioid dependent subjects – a 99mTc-TRODAT-1SPECT imaging and genetic association study. (30th November 2020) - Grover, Tripti; Gupta, Ranjan; Arora, Geetanjali; Bal, Chandra Shekhar; Ambekar, Atul; Basu Ray, Subrata; Vaswani, Meera; Sharma, Arundhati
Highlights: Dopamine transporter regulates dopamine levels through epigenetic mechanisms. SPECT/CT revealed significantly reduced DAT availability in AD compared to controls. Significant increase in DAT promoter methylation in AD compared to controls and OD. DAT1 promotermethylation in AD significantly associated with lower TRODAT-1 uptake. Abstract: Drug dependence associated with increased dopamine neurotransmission and neuroplastic changes is influenced by Dopamine transporters (DAT) which are modulated by genetic and epigenetic factors. This study assesses DAT availability in relation to the 40bp DAT1 VNTR (genetic) and DAT1 promoter methylation (epigenetic) changes in patients with alcohol dependence (AD) and opioid dependence (OD). A total of 60 subjects ( n =20 each of AD, OD and controls) were recruited. SPECT/CT imaging using 99m Tc-TRODAT-1 was performed for measuring striatal DAT availability and DNA screened to check DAT1 promoter methylation and 40bp VNTR polymorphism. SPECT/CT imaging revealed significant decrease in DAT availability in the striatum and putamen and significant increase in DAT1 promoter methylation in AD compared to control and OD. The 40bp VNTR distribution was similar in all three groups with 10repeat and 9repeat alleles being the most common. The AD individuals with DAT1 promoter methylation showed significantly lower TRODAT-1 uptake compared to the ones with no methylation. AD individuals homozygous for the 10repeat VNTR also showed reduced DAT availability. This is the first imaging study using 99m Tc-TRODAT-1 from India documenting significantly reduced striatal DAT availability, increased DAT methylation and frequency of 10repeat individuals associated with decreased DAT availability in AD.